Hopf algebra structure on superspace SPq2|1 - Celik, Salih (HACETTEPE UNIV, FAC SCI, 2020)
Super-Hopf algebra structure on the function algebra on the extended quantum symplectic superspace SPq2 vertical bar 1, denoted by F(SPq2 vertical bar 1), is defined. A quantum Lie superalgebra derived from F(SPq2 vertical bar 1) is explicitly obtained.
Keywords: quantum symplectic superspace; super star-algebra; super-Hopf algebra; quantum supergroup; quantum Lie superalgebra; DEFORMATION; Mathematics